ANALYSIS OF PNEUMONIA INCIDENT BASED ON AGE GROUP IN BAHTERAMAS HOSPITAL 2020-2022 - Sunarto, I Nengah; Tosepu, Ramadhan (Universitas Halu Oleo, 2024)
ABSTRACT Pneumonia is a condition where there is infection or acute inflammation of the lung tissue caused by various microorganisms such as bacteria, viruses, parasites, fungi, exposure to chemicals, or physical damage to the lungs. Pneumonia can infect all age groups. The aim of this study was to determine the age category that had the highest incidence of pneumonia at Bahteramas RSU. The method used is analyzing secondary data obtained from Bahtermas hospital. The method used is to analyze secondary data using the miroscoft excell application. The analyzed data was obtained from the results of a survey conducted by researchers at Bahteramas Hospital. Division of age groups based on Department of Health RI categories. The categories used are toddlers (0-4 years), children (5-14 years), teenagers (15-25 years), adults (26-45 years), elderly (46-65 years) and seniors (65 and over). The research results show that the average number of cases in 2020- 2022 for the groups under five, children, teenagers, adults, elderly and seniors respectively was 45.2%, 10.8%, 4.1%, 9.8%, 17.9%, 12.2%. Based on the research results, it can be seen that pneumonia in the toddler category has the highest incidence rate from 2020-2022 at RSU Bahteramas with an average rate of 45.2%. Based on the results of this study, it is hoped that future studies can develop risk factors for pneumonia based on other categories Keywords: pneumonia, risk factors and toddler pneumonia